Increased Immunity against the Oral Germs Porphyromonas gingivalis and Prevotella intermedia in Different Categories of Juvenile Idiopathic Arthritis - Franck Zekre; Rolando Cimaz; Mireille Paul; Teresa Giani; Louis Waeckel; Anne-Emmanuelle Berger; Jean-Louis Stephan; Myriam Normand; Stéphane Paul; Hubert Marotte (Biomedicines, 2022)
(1) Background: The link between periodontal disease and rheumatoid arthritis (RA) is now widely reported. Several studies suggest the role of Porphyromonas gingivalis (P. gingivalis) in the pathophysiology of RA and some observations highlight the improvement of the disease activity induced by therapies against P. gingivalis. We have very little data on the prevalence of P. gingivalis carriage in patients with juvenile idiopathic arthritis (JIA) and its possible involvement in the pathophysiology of inflammatory joint diseases in children. (2) Methods: The specific IgG responses against P. gingivalis and Prevotella intermedia (P. intermedia) were determined in a cohort of 101 patients with JIA and 19 patients with other autoimmune diseases (inflammatory bowel disease and type 1 diabetes). (3) Results: Specific anti-P. gingivalis and anti-P. intermedia IgG titers were higher in JIA group than in control groups. These differences were mainly observed in the oligoarthritis group. The same pattern was observed in enthesitis-related arthritis (ERA). (4) Conclusions: Children with oligoarticular and ERA subsets had higher IgG titers to P. gingivalis and P. intermedia. These results suggest involvement of an oral dysbiosis in the occurrence of JIA in these subgroups.